Biochar: a sustainable solution for solid waste management in agro-processing industries. Issue 2 (7th February 2021) - Dahal, Raj Kumar; Acharya, Bishnu; Farooque, Aitazaz
ABSTRACT: Agro-processing is a major industry in Canada. The processing of an agricultural product generates an enormous amount of water and solid waste. Appropriate management of these waste streams has become a challenging issue. The present study proposes a concept of circular bio-economy whereby solid waste from one agro-processing industry is used as a feedstock for producing biochar, which is then used in another agro-processing industry for wastewater treatment. The biochar after wastewater treatment can be used for agricultural soil applications. This article describes a study on the pyrolysis of oilcakes from crambe and meadowfoam seeds. The pyrolysis of oilcakes obtained from crambe and meadowfoam seeds is conducted in a furnace-heated reactor at 450 °C and 550 °C and the properties of char, oil and gas are studied. The biochar is then used for wastewater treatment. This article discusses the results.